Distribution and habitats of forked aster (Aster furcatus), a threatened Wisconsin plant - (:unkn) unknown (My University, 1991)
We describe the locations and habitat characteristics of 10 of the 14 known populations of Aster furcatus in Wisconsin. We were unable to identify any particularly unusual features of A. furcatus habitats which could be related to its rarity. The rarity of forked aster is probably not related to specialized habitats, but is most likely the result of requirements for moderate disturbance, inability to withstand competition, poor reproduction from seed, and low genetic variance.
Keywords: forked aster; Aster furcatus; habitat; distribution